Low regularity function spaces of N-valued maps are contractible - Mironescu, Petru (MATHEMATICA SCANDINAVICA, 2017)
Let M be a compact Lipschitz submanifold, possibly with boundary, of R ^n. Let NR ^k be an arbitrary set. Let s0 and 1p<∞ be such that sp<1. Then W^s, p(M ; N) is contractible.